Optimization Of Social Media Marketing For MSMEs In Makassar City: Optimization Of Social Media Marketing For MSMES In Makassar City - ashdaq muhammad; Nur Isra' Ahmad; Sri Asmirani (Journal of Economic, Public, and Accounting (JEPA), 2025)
This study aims to analyze and optimize the implementation of social media marketing at Mammiri MSMEs in Makassar City, a medium-sized enterprise specializing in passion fruit beverages marketed to the general public and distributed to souvenir shops across the city. The research is significant because Mammiri MSMEs have encountered challenges in enhancing their social media marketing strategies, which they perceive as having limited impact on sales performance. An action research approach was employed, following the P-Process model, wherein the researchers were actively involved in evaluating the effectiveness of social media platforms in improving brand awareness, customer engagement, and sales. The intervention focused on strengthening visual identity, integrating various social media platforms, utilizing platform-specific features, and designing 14 pieces of content published on the enterprise's Instagram and Facebook accounts to optimize digital marketing performance. The findings indicate that the implementation period from February to July 2025 resulted in a 22.54% increase in Instagram followers and a 7.83% increase on Facebook. Instagram engagement rose by 27.78%, while Facebook engagement increased by 7.43%. Moreover, sales grew by 49.34%, and repeat orders increased by 53.06%. These results are expected to provide valuable insights for optimizing the future social media marketing strategies of Mammiri MSMEs.